Solve dy/dx + yx = y2e^(x^2/2)sinx
"\\frac{dy}{dx}+yx=y^2e^{\\left(\\frac{x^2}{2}\\right)}\\sin \\left(x\\right)"
First order Bernoulli Ordinary Differential Equation
A first order Bernoulli ODE has the form of "y'+p\\left(x\\right)y=q\\left(x\\right)y^n"
Substitute "\\frac{dy}{dx}\\mathrm{\\:with\\:}y'\\:"
"y'\\:+yx=y^2e^{\\left(\\frac{x^2}{2}\\right)}\\sin \\left(x\\right)"
Rewrite in the form of a first order Bernoulli ODE: "y'+p\\left(x\\right)y=q\\left(x\\right)y^n"
"p\\left(x\\right)=x,\\:\\quad q\\left(x\\right)=e^{\\frac{x^2}{2}}\\sin \\left(x\\right),\\:\\quad n=2"
The general solution is obtained by substituting "v=y^{1-n}"
and solving "\\frac{1}{1-n}v'+p\\left(x\\right)v=q\\left(x\\right)"
Transform to "\\frac{1}{1-n}v'+p\\left(x\\right)v=q\\left(x\\right):" "-v'+xv = e^{\\left(\\frac{x^2}{2}\\right)}\\sin \\left(x\\right)"
Solve "-v'+xv = e^{\\left(\\frac{x^2}{2}\\right)}\\sin \\left(x\\right)" : "v = e^{\\large\\frac{x^2}{2}}cos(x) + c_1 e^{\\large\\frac{x^2}{2}}"
Substitute back "v = y {-1}:" "y^{-1} = e^{\\large\\frac{x^2}{2}}cos(x) + c_1 e^{\\large\\frac{x^2}{2}}"
Isolate y : "y = \\large\\frac{1}{e^{\\frac{x^2}{2}}\\left(\\cos \\left(x\\right)+c_1\\right)}"
The answer: "y = \\large\\frac{1}{e^{\\frac{x^2}{2}}\\left(\\cos \\left(x\\right)+c_1\\right)}"
Comments
Leave a comment